2016
DOI: 10.23917/varidika.v28i1.2402
|View full text |Cite
|
Sign up to set email alerts
|

Penanaman Sikap Cinta Tanah Air dalam Pramuka di Dabin 5 UPTD Pendidikan Wirosari Brobogan

Abstract: The purpose of this study was to describe the attitude of patriotism planting in extracurricular activities scouts on the General Terms and Conditions Skills Special Skills in Dabin 5 UPTD Wirosari Subdistrict Grobogan. Type used is ethnographic qualitative research design. The research subjects were principals, teachers, and students. Data collection techniques used interviews, observation, and documentation. Data analysis techniques used the analysis of the flow of the process of data collection, data reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 1 publication
0
3
0
5
Order By: Relevance
“…Third, putting common interests ahead of personal or class interests (Apriani, 2017;Ulfah, 2015). Fourth, acknowledge and fully appreciate the diversity within the Indonesian nation (Ikhsan, 2017;Priyoutomo, 2016;Yuliarni, 2021). Fifth, willing to maintain and contribute to the advancement of the state and preserve the good name of its nation (Abu Bakar et al, 2018;Adli & Fatimah, 2019;Saragih et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, putting common interests ahead of personal or class interests (Apriani, 2017;Ulfah, 2015). Fourth, acknowledge and fully appreciate the diversity within the Indonesian nation (Ikhsan, 2017;Priyoutomo, 2016;Yuliarni, 2021). Fifth, willing to maintain and contribute to the advancement of the state and preserve the good name of its nation (Abu Bakar et al, 2018;Adli & Fatimah, 2019;Saragih et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nationalism is the unity between the will for unity and independence based on ethical values (Aeni, 2018;Musafiyono, 2014;Retnasari & Hidayah, 2020;Widnyani et al, 2015). Nationalism is an understanding, which holds that the highest allegiance of the individual must be surrendered to the national state (Ikhsan, 2017;Priyoutomo, 2016;Yuliarni, 2021). Students in elementary school age and students in a golden age to be imbedded with such social values and norms as nationalistic values.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by (Putri, 2017) also found that the character values in scouting obtained by students were love of nature, loving each other, having a patriot spirit, polite, knight, obedient, deliberate, willing to help, steadfast, diligent, skilled, happy, careful, modest, discipline, courageous, loyal, responsible, trustworthy. Scouting also instills character values because each activity is designed to teach about independence and implements the cultivation of independent attitudes of students in the alert and group groups through scouting extracurricular activities (Priyoutomo, 2016;Purwaningsih, 2017). The inculcation of five attitude character values through scouting extracurricular activities has been well implemented.…”
Section: Resultsmentioning
confidence: 99%
“…Cinta tanah air juga perasaan yang timbul dari dalam hati sanubari seorang warga negara terhadap tempat kelahiran atau tanah airnya untuk mengabdi, memelihara, membela, melindungi tanah airnya dari segala ancaman dan gangguan (Suhayah dkk, 2013). Cinta tanah air merupakan pengamalan dan wujud dari sila Persatuan Indonesia yang dapat diwujudkan dalam kehidupan sehari-hari di keluarga, sekolah, dan masyarakat (Priyoutomo dan Ngalim, 2016). Sesuai dengan hasil penelitian yang terjadi pada siswa SDN 3 Padurenan, dimana siswa diajarkan untuk selalu menjaga rumah masingmasing agar tetap bersih serta mengenalkan lagu-lagu nasional maupun lagu daerah melalui grup WhatsApp (pembiasaan saat pembelajaran).…”
Section: Pendahuluanunclassified